Advanced manufacturing techniques in shipyards - Turan, Eda; Celebi, Ugur Bugra (CRC PRESS-TAYLOR & FRANCIS GROUP, 2012)
Maritime business has a strategic position in the World and shipbuilding is one of its most significant part. However, the global financial crisis has also affected the shipyards dramatically. Some projects were not managed to be completed while some of them have been cancelled. In spite of this, on the other hand shipyards are trying to make new vessel agreements in order to continue their activities and also go on construction of on-going projects. Due to some projects that have been cancelled/postponed, not only current projects are under risk and pressure of factors such as cost effectiveness, time savings but also new contracts are under risk nowadays. Therefore shipyards should take some precautions to stay competitive in this uncertain situation. One way of delivering the vessels on time and cost effectively is to apply project management system in the shipyards and control its outputs periodically. In addition to this, some shipyards invest on their manufacturing processes in order to increase productivity. In this context, establishing production lines in order to speed up their production capacity, reducing the costs and delivery times by mass production, increasing the profits from each vessel can be listed. Environmental protection is also a major issue during the shipbuilding period. Usage of robotic welding processes and automated technologies for reducing the wastes and pollutants sourced by the shipyard processes can be beneficial for preserving the environment and improving the production quality. In this paper, the manufacturing processes of the shipyards are investigated; the benefits of implementing advanced manufacturing techniques in the shipyards considering environmental issues are presented.
Keywords: Shipyards; Manufacturing Techniques; Shipbuilding; Production; Engineering